Analisis Pengaruh Harga, Brand Image, dan Promosi terhadap Keputusan Pembelian pada Produk Fashion Boolao di Platform Shopee - Dani Rizki; Muhamad Hammam Faisal Hakim; Raifan Ridki Nuf’Fallah; Yusup Yusup; Erna Herlinawati (Jurnal Manajemen Riset Inovasi, 2026)
The intense rivalry among homegrown fashion labels within e-commerce networks compels corporate leaders to refine their marketing mixes to sustain consistent sales. This study examines how financial cost, brand perception, and promotional efforts partially and collectively determine consumer buying preferences for Boolao, a local fashion brand operating on Shopee. Utilizing a quantitative methodology with descriptive and verifying traits, this research gathered empirical data from 100 Shopee subscribers acquainted with Boolao's catalog via targeted questionnaires. Samples were selected using a purposive framework, followed by data processing via multiple linear regression techniques utilizing IBM SPSS Statistics 25. The empirical outcomes demonstrate that on a partial level, pricing plays the most dominant positive role in driving transaction decisions, with brand identity and marketing outreach close behind in substantial positive significance. Jointly, these three independent aspects account for 76.4% of the shifts in consumer final choices. These insights offer operational references for Boolao’s management to formulate strategic price positioning, build robust brand recall, and establish interactive e-marketing campaigns on Shopee for long-term customer conversion.